Cerita Lisan Lukisan Bunuh Diri Raden Saleh Sebagai Inspirasi Penciptaan Tari Rundung Saleh - Ida Bagus Ketut Sudiasa; Tuteng Suwandi; Hendrik, Putri Annisa (Program Studi Pendidikan Tari FBS UNJ, 2022)
Bullying is a situation where a person or a group of people abuse their power. Saleh is taken from the name of the inspirational figure, Raden Saleh Syarif Bustaman. Rundung Saleh depicts a story of bullying experienced by Raden Saleh Syarif Bustaman. The correlation of the title and the story of bullying experienced by Raden Saleh is that bullying still happening nowadays. The